Perkawinan PERKAWINAN WANITA HAMIL AKIBAT ZINA: ANALISIS STATUS ANAK MENURUT HUKUM ISLAM DAN HUKUM POSITIF (STUDI KASUS DI PALAS, BENDUNGAN, CILEGON): Perkawinan, Hamil Akibat Zina, dan Status Anak - Ahmad Sayidi, Ahmad Sayidi; Sayehu; Musthofa, Usman (JAS : Jurnal Ahwal Syakhshiyyah, 2024)
The marriage of pregnant women due to adultery is a very worrying problem, especially the problem in the Palas neighborhood, Bendungan Village, Cilegon District, Cilegon City. This research problem is important because it impacts the rights and legal protection of the individuals involved. Therefore, this research aims to discuss: the community's views on this case, the legal consequences for children born from this marriage, and the obstacles faced by women pregnant as a result of adultery in accessing legal rights and protection in the Palas environment. The research method used is qualitative, with a case study approach. Data was collected through in-depth interviews and observations of the community in the Palas area. Data analysis was carried out thematically to identify patterns of views, legal impacts and obstacles faced. Based on the research results, it can be concluded: The views of the Palas Environmental community reflect the complexity of values, norms and beliefs that shape their perspective on the marriage of women who become pregnant as a result of adultery. The diversity in views suggests that a holistic approach and taking into account local cultural and social context is needed to understand the complex dynamics involved in this issue. The legal consequences of children born from marriage resulting from adultery are related to guardianship and inheritance according to Islamic Law and Positive Law, reflecting the complexity and duality in the legal position of children. The need for cooperation between the Islamic legal system and civil law to accommodate children's rights fairly and fairly is important in ensuring optimal protection of the rights of children born from this situation. Then, women who become pregnant as a result of adultery in the Palas area face a number of various obstacles and barriers in accessing legal rights and protection. Efforts to overcome this obstacle require a holistic approach involving the community, government and relevant institutions so that women's rights can be guaranteed and fair legal protection can be accessed optimally.